PENGARUH SELF-EFFICACY DAN DISIPLIN KERJA TERHADAP KINERJA GURU DIMEDIASI KOMITMEN ORGANISASIONAL PADA SMK NEGERI DI KABUPATEN PATI (Jurnal Mahasiswa Pasca Sarjana, 2013)
This study to analyze the effect of Self Efficacy and Work Discipline to Teacher Performance with Mediation Organizational Commitment. Population is used as the object of the teachers in SMK Pati totaling 221 people. Sampling was purposive sampling methods that sample selected according to criteria that are determined to be the respondent. From the results of purposive sampling can be seen that the number of samples in this study were 203 respondents. The results prove that the model's ability to correctly describe the effect of variable Self Efficacy and Organizational Commitment to Work Discipline is 54.4%. While others described by 45.6% to a variable outside the regression model. Self Efficacy and Effects, Work Discipline, Organizational Commitment to Teacher Performance by 69.5%. While the other 30.5% is explained beyond this regression model. Self Efficacy with Mediation Organizational Commitment does not have a significant impact on teacher performance in SMK Pati. Mediation test results note that the value is greater than the direct effect of the indirect effect.Discipline Working with Organizational Commitment mediation proved to have a significant impact on teacher performance in SMK Pati. The test results prove the direct influence of greater value than the value of the indirect effect.Keywords: Teacher Self-Efficacy, Work Discipline, Organizational Commitment, Teacher Performance